In-situ optical diagnostics of boron-doped diamond films growth - Kraszewski, Maciej; Bogdanowicz, Robert (Photonics Letters of Poland, 2013)
Interferometry is desirable method for in-situ measurement of thin, dielectric film growth, as it don’t modify conditions of film deposition. Here we present interferometrical measurements of thickness of doped diamond films during Chemical Vapor Deposition (CVD) process. For this purpose we used semiconductor laser with 405 nm wavelength. Additional ex-situ measurement using spectral interferometry and ellipsometry have been performed. We found that doping diamond with boron does not cause degradation of interference of light inside the film. To our knowledge this is first study of optical monitoring of boron doped, polycrystalline diamond films deposition. Full Text: PDF References J. Asmussen, D. Reinhard, Diamond Films Handbook, 1st ed. (CRC Press 2002). CrossRef R. S. Sussmann, CVD diamond for electronic devices and sensors. (Chichester, U.K.: J. Wiley 2009). CrossRef E. Bakker, Y. Qin, "Electrochemical Sensors", Anal. Chem. 78, 12 (2006). CrossRef V. Prajzler et al., "Design and investigation of properties of nanocrystalline diamond optical planar waveguides", Opt. Express 21, 7 (2013) CrossRef N.J. Alberto et al., "Nanodiamond coated Bragg gratings for sensing applications", Proc. SPIE 8421 (2012). CrossRef R. Bogdanowicz et al., "Nucleation and growth of CVD diamond on fused silica optical fibres with titanium dioxide interlayer", Phys. Status Solidi (a) 210, 10 (2013). CrossRef M. Smietana et al., "Application of diamond-like carbon films in optical fibre sensors based on long-period gratings", Diamond Relat. Mater. 16, 4 (2007). CrossRef R. Bogdanowicz et al., "Amperometric sensing of chemical oxygen demand at glassy carbon and silicon electrodes modified with boron-doped diamond", Sens, Actuator B-Chem. 189 (2013) CrossRef C.E. Nebel et al., "Diamond and biology", J. R. Soc. Interface 4, 14 (2007). CrossRef R. Bogdanowicz et al., "Influence of the boron doping level on the electrochemical oxidation of the azo dyes at Si/BDD thin film electrodes", Diamond Relat. Mater. 39, (2013). CrossRef J.J. Gracio et al., "Diamond growth by chemical vapour deposition", J. Phys. D: App. Phys. 43, 37 (2010). CrossRef J. Luo, X. Ying, P. Wang, L. Chen, "Study on the growth of CVD diamond thin films by in situ reflectivity measurement", Diamond Relat. Mater. 11, 11 (2002). CrossRef A.M. Bonnot, R. Schauer, B. Weidner, "HFCVD diamond film nucleation and growth studies by in-situ optical technique and ex-situ AFM observations", Diamond Relat. Mater., 7, 2 (1998). CrossRef C.D. Zuiker, D.M. Gruen, A.R. Krauss, "In situ laser reflectance interferometry measurement of diamond film growth", J. Appl. Phys. 79, 7 (1996). CrossRef M. Bass et al., Handbook of opitcs, Volume IV: Optical Properties of Meterials, Nonlinear Optics, Quantum Optics (McGraw-Hill 2009). E.D. Palik ed., Handbook of Optical Constants of Solids (Elsevier 1998). D.I. Siapkas, C.L. Mitsas, "Generalized matrix method for analysis of coherent and incoherent reflectance and transmittance of multilayer structures with rough surfaces, interfaces, and finite substrates", Appl. Opt. 34, 10 (1995). CrossRef C. Katsidis, D.I. Siapkas, "General Transfer-Matrix Method for Optical Multilayer Systems with Coherent, Partially Coherent, and Incoherent Interference", Appl. Opt. 41, 19 (2002). CrossRef